Tree-crop Interactions in Agroforestry Systems: a Brief Review - Basavaraju, T. B.; Gururaja Rao, M. R. (Indian Forester, 2000)
Integration of trees in agroforestry system results in positive or negative interactions between trees and crops. Micro-climate amelioration and maintenance or improvement in soil productivity are the major positive interactions while competition for light, water and nutrients, and allelopathy are the major negative interactions in agroforestry systems. The balance between negative and positive interactions determines the over all effect of interactions in a given agroforestry system. Selection of suitable tree species for agroforestry is important, however many a times it is not possible to select tree species having all the desirable characters for agroforestry because of different production or protection goals. In such situations agroforestry systems have to be managed through planting optimum density of trees, proper spatial arrangement and pruning and thinning of tree crowns and roots to reduce the negative effects of trees.